STRATEGI PENYEBARLUASAN ILMU HUKUM MELALUI SASTRA - Murti Ayu Hapsari; Murtini Murtini (Haluan Sastra Budaya, 2021)
Novels are one of the literary genres that utilize language. In this case, the use of language in literary or literature, according to Umar Kayam, is not about using it correctly or not, but rather whether or not that language appropriate for specific occasion. Likewise, legal science cannot separate itself from language in terms of its application. Language in law of legal filed has its own variety which often makes it difficult for people who are not directly involved in it to grasp its certain meanings. This is because language in law require that it can conveyed in a concrete, straightforward manner, so that it will not lead to many ambiguous interpretations. It can be said that the use of language form in these two domains is in very opposite direction. Novel written by Agus Sardjono, "Legal Research: A Novel on Legal Research Methods" tries to unravel these difficulties by using literary as tools specifically to facilitate students of university  in understanding and applying legal research methods. This paper will further describe the novel in two perspectives; legal point of view and literary point of view. The novel "Legal Research" proves that literature is a  very broad as a medium, that can be used to describe various field of expertise such as history, psychology, politics, including law.